Essential radio journalism how to produce and present radio news - Chantler, Paul (Professional media practice, 2009)
'Incredibly comprehensive. Learn and understand this lot and you will have a fine grasp' Jon Snow 'This sets the standard for every radio newsroom' - Andy Ivy, Editor, Sky News Radio In an age of infinite choice made possible by new technology, and a disturbing move away from traditional reporting into colourful comment and speculation by blogs and 'citizen journalists' there has never been a better time to focus on pure journalism skills. Essential Radio Journalism is a vastly comprehensive working manual for radio journalists as well as a textbook for broadcast journalism students. It contains.